SCIENCE TEACHERS AT THE UPPER PRIMARY LEVEL IN DIRECT CONVERSATION WITH TEXTBOOK DEVELOPER DURING VIDEO-CONFERENCING: AN EXPERIENCE - Verma, Ruchi; Patel, Madhulika S. (SCHOOL SCIENCE, 2014)
In education system, there has to be congruence among policy statement, curriculum, syllabus and content in textbooks .The introduction of changes needs comprehensive planning, but as no planning is perfect, introduction of changes needs not wait too long. Similarly, it is found that curriculum misses some policy initiatives, syllabus misses some aspects of curriculum and textbooks misses some aspects of syllabus. Hence, periodic reviews should be undertaken to identify gaps and missing links. In the sequence of curriculum revision, this was the fourth revision of curriculum which made available National Curriculum Framework–2005 (NCF–2005) in our hands.The NCF–2005 has significantly altered the perspective on subject content in the light of constructivist approach to teaching-learning, by giving emphasis on the development of critical thinking and self-reflection abilities among students. The major thrust is given on enhancing comprehension of children in the classroom and integration of evaluation within the teachinglearning process. The foundation of success of any planning is not laid only through the involvement of educational planners, teachers, experts, representatives of the government and non-government organisations, but the voice of layperson is equally important. Hence, the process of further revision of curriculum was open to everybody for the inclusion of their views as well as of their feedback about the current scenario. After revision of curriculum, the syllabi in different areas were developed with the spirit to make an attempt to eradicate the problem of loaded bags.